Analisis Kontribusi Pengemudi Becak Wisata dalam Meningkatkan Pariwisata Syariah Kota Padangsidimpuan dengan Pendekatan Quadruple Helix - Hasibuan, Masdelima; Nawawi, Zuhrinal; Tambunan, Kharina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study discusses the contribution of pedicab drivers in increasing sharia tourism in the city of Padangsidimpuan through the support of several stakeholders such as the Government, Academicians, Businessmen, and Civil Society or better known as the Quadruple Helix. This study uses a descriptive qualitative approach where the purpose of descriptive is a formulation of the problem that directs research to be able to explore social situations that will be studied broadly, thoroughly, and in depth. The results of this study indicate that the contribution of tourist pedicab drivers in the development of sharia tourism in the city of Padangsidimpuan with the support of the Quadruple Helix role can be seen from the launch of the tourist pedicabs which are a form of effort to increase the attractiveness of tourists to travel to the city of Padangsidimpuan. With the existence of these tourist pedicabs, tourist visits to the city of Padangsidimpuan have also increased after a decline due to the impact of the pandemic in 2019. In addition, tourist pedicab drivers are also provided with training and understanding by experts on the rules that apply when bringing tourists to destinations. -existing tourist destinations and these are in accordance with the provisions of the Shari'a. Not only tourist pedicab drivers, the government, businessmen, and the community there also work together in providing facilities that support Islamic tourism activities. So with this it is hoped that the sharia tourism sector in the city of Padangsidimpuan can continue to develop in the future.